Public-Private Partnerships in transport: a critical assessment of the Caribbean - Laura Panadès-Estruch (Public Administration and Policy, 2021)
Purpose – This article critically analyses the extent to which selected Public-Private Partnerships (PPPs) transportation projects in the Caribbean subregion embrace good practices and how they benefit the public sector. Design/methodology/approach – The article begins with the general rationale of PPPs, leading to a discussion on the specific challenges of the Caribbean subregion and an assessment of certain critical projects. The sample cases include the L F Wade International Airport in Bermuda, the cruise berthing and cargo port redevelopment project in the Cayman Islands, and the Sanger International Airport in Jamaica. There are five aspects to the critical assessment: (a) an evaluation of the type of PPP arrangement used; (b) the legal/policy framework; (c) financial implications; (d) accountability; and (e) miscellaneous data. Desk-based research is conducted as supported by both international and local sources to convey a uniquely local perspective in this under-researched area of scholarship. Findings – PPP frameworks in the Caribbean are improving quickly but remain a work in progress. Jamaica leads the region. Bermuda trails behind. Problems of legal compliance with frameworks and limited market engagement persist, leading to risk management problems. Originality/value – This article fills a literature gap on critical analysis of individual Caribbean PPP transportation projects. Previous reports, mostly by international organisations, cover regional or sectorial trends. Other sources take a descriptive but not critical approach.